Penerapan Data Mining untuk Menemukan Pola Asosiasi Aktivitas Belajar dan Prestasi Santri Menggunakan Algoritma Apriori - Hudawi, Ahmad; Anam, Khoirul; Rahman, Miftahur (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Education in Islamic boarding schools is unique, integrating cognitive, character, and spiritual development. This study aims to uncover the relationship between students' learning activities and academic achievement using data mining techniques with the Apriori algorithm. A quantitative approach was applied, analyzing data on learning activities and academic performance. Data preprocessing and the Apriori algorithm were employed using RapidMiner software to identify association patterns between variables. Findings indicate a significant relationship between class attendance, study hours, discussion participation, and extracurricular achievements with academic performance. The association rules revealed that consistent attendance and active learning participation positively influence academic achievement, with confidence levels of 70-80% for "Good" performance categories. This study offers actionable insights for Islamic boarding schools to design more effective learning strategies and emphasizes the potential of data-driven education to enhance student outcomes..